Assess the effect of population control programs on National HeaIth Development in Islamic Republic of Iran (1986-1998) - F. Dabbaghi (Iran University of Medical Sciences, 1998)
This survey is a descriptive analytic study which was carried out to assess the effects of population control programs on National Health Development in Islamic Republic of Iran (1986-1998). The objectives of the study are: 1)To determine the effects of family planning program on National Health Development ( 1986-1998). 2)  To indicate the relationship between family planning coverage and some health indicators. This study was conducted at two stages: 1)  Presentation of a simulation modle 2)  Prediction of population size by large scale clinical trial (1986-1998). Prediction method is used to determine the differences of population at two stages: 1)  Stability of total fertility rate (5.6) 2)  Gradual decrease of total fertility rate. The findings show that stability of T.F.R and decrease in developmental indices (such as literacy of women and employment of women) has led to an increase in population size (17494391) has added to population between (1986-1998). By T.F.R gradual decrease and other developmental indices increase, population size increase to 563228415 between (1986-1998). In this survey by using the results of simulation and health indicators the relationship of Health variables and family planning coverage is computed. Findings show that: 1)  There is a significant relationship between the health variables and family planning coverag. 2) There is a positive significant correlation between family planning coverage and 1M.R., under 5 mortality rate and crude death rate. 3) There is a significant correlation between literacy of women, employment of women and marriage. 4) Other findings emphasize the significant relationship between family planning coverage and immunization of children.